PENGARUH KECAKAPAN DIGITAL SISWA SMP NEGERI 1 BATANG KABUPATEN JENEPONTO TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA - Annisa Nurdin; Abd Halling; Citra Rosalyn Anwar (STKIP Subang, 2023)
Students have smartphones and are able to use every application they have on their smartphones such as communication applications, online games, social media and the like. The aim of this research is to measure the digital abilities or skills possessed by students and how students use them, to show an overview of the implementation of the learning process involving students' digital abilities or skills in Indonesian language subjects and to find out whether there is an influence on the digital skills of students at SMP Negeri 1 Batang Jeneponto Regency on student learning outcomes in Indonesian language subjects. This research was conducted using a quantitative approach with a type of research that used a quasi-experimental type with a method that only used one treatment group and did not use a control group. The sample from this research was 25 students from class VIII. The instruments in this research use questionnaires, tests (assignments) and documentation as support for this research. The questionnaire consists of a pretest given before the learning process is carried out and a posttest given after the learning process is carried out, while the test consists of tasks containing news text and poetry text material. Data analysis uses descriptive statistical analysis and inferential statistical analysis with hypothesis testing using the t-test. Based on the results of data analysis and t-test, the average value of students' abilities and learning outcomes after the implementation of the learning process involving students' digital skills was higher than before the implementation of the learning process involving students' digital skills. All students involve digital skills by using several methods of using search engines and social media in completing assignments with news text and story text material. The results of this research show that there is an influence on the digital skills of students at SMP Negeri 1 Batang Jeneponto Regency on student learning outcomes in Indonesian language subjects.